(untitled) (Precision Medicine Communications, 2023)
DPYD (dihydropyrimidine dehydrogenase) genotyping is relevant in the context of cancer treatment, particularly with fluoropyrimidine-based chemotherapy drugs such as 5-fluorouracil (5-FU) and capecitabine. Dihydropyrimidine dehydrogenase is an enzyme involved in the metabolism of these drugs, and certain genetic variants in the DPYD gene can lead to reduced enzyme activity, potentially causing severe and life-threatening toxicities. The implementation of upfront DPYD genotyping involves testing patients for specific DPYD variants before starting fluoropyrimidine-based chemotherapy. Pinheiro and colleagues assessed the frequency of the four most common and well-established DPYD variants associated with fluoropyrimidine toxicity and implemented a relatively low-cost and high-throughput genotyping assay for their detection. Their study comprised 457 patients that were genotyped for the DPYD c.1129-5923C>G, c.1679T>G, c.1905 + 1G>A and c.2846A>T variants, either by Sanger sequencing or kompetitive allele-specific PCR (KASP) technology. Of these, 172 patients presented toxicity during treatment with fluoropyrimidines (post-treatment group), and 285 were tested before treatment (pretreatment group). A little more than 7% of patients were DPYD homozygous. The most common variant they found was c.2846A>T. The KASP assays designed in this study presented 100% genotype concordance with the results obtained by Sanger sequencing. The authors concluded that the combined assessment of the four DPYD variants increases the identification of patients at high risk for developing fluoropyrimidine toxicity. They also found KASP genotyping a low-cost and rapid turnaround time assay. Pharmacogenet Genomics. 2023 Oct 1;33(8):165-171. doi: 10.1097/FPC.0000000000000505.